Determinación de los factores que inciden en la disolución y liquidación de las compañías por sector económico de la provincia de El Oro periodo 2015-2020 - Alvarado Sánchez, Tamara Yaritza (2022)
The present work titled, “THE DETERMINATION OF THE FACTORS THAT AFFECT THE DISSOLUTION AND LIQUIDATION OF COMPANIES FOR ECONOMIC AREA IN EL ORO PROVINCE PERIOD 2015-2020”; it was develop with the main goal to let know the factors that affect the dissolution and liquidation of the companies for the economic area in El Oro Province period 2015-2020. The information of the companies who were in this process of dissolution and liquidation in the economic area in the province El Oro period 2015-2020 was check through the official web site of Superintendence of securities and insurance companies; the legal base that was used: Company Law, Dissolution, Liquidation and Companies Reactive law; through National Classification guide it was checked the economic activities, based on their social reason. The information of the companies that were in these process of dissolution and liquidation for economic area in the period 2015-2020, it was obtain from data base SUPERCIAS, organizing the information of El Oro province, due the legal situation taking into account the last balance presented in this period. To build the data base of Companies that were in these process of dissolution and liquidation according to the economic area take into account the leading indicators in El Oro province during 2015-2020; the financial states were download form the official web site SUPERCIAS, classifying according to the Single Catalog of Accounts (CUC), after that the list of companies was done in El Oro Province, named in each column of Excel sheet the corresponding name of the different accounts, some dynamic tables were made to show the information to let people know which were the causes of dissolution and liquidation and let them to analyse the information, then the financial and economic situation of the companies were establish. The main financial indicators were applied, through them was possible to measure the current liquidity, average working capital ratio, equity indebtedness index, average rate return of equity (ROE) average rate of return on assets (ROA)